2017
DOI: 10.1371/journal.pone.0174707
|View full text |Cite
|
Sign up to set email alerts
|

A tetrameric peptide derived from bovine lactoferricin as a potential therapeutic tool for oral squamous cell carcinoma: A preclinical model

Abstract: Oral squamous cell carcinoma is the fifth most common epithelial cancer in the world, and its current clinical treatment has both low efficiency and poor selectivity. Cationic amphipathic peptides have been proposed as new drugs for the treatment of different types of cancer. The main goal of the present work was to determine the potential of LfcinB(20–25)4, a tetrameric peptide based on the core sequence RRWQWR of bovine lactoferricin LfcinB(20–25), for the treatment of OSCC. In brief, OSCC was induced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
3
13
0
2
Order By: Relevance
“…30,31 On the other hand, this peptide also exhibited a selective cytotoxic effect against OSCC-derived cell lines CAL-27 (IC 50 ¼ 9 mM) and SCC15 (IC 50 ¼ 9 mM), while the peptide's cytotoxic effect against the non-tumorigenic cell line was moderate. 28,29 It can be seen that these IC 50 values are of the same order of magnitude as those obtained for MCF-7 cells, which conrms that the peptide exhibited signicantly selective cytotoxic effect against human cell lines derived from breast and oral cancer. The cytotoxic effect of the peptide against MCF-7, CAL-27, and SCC-15 cancer cells continues for 24 h aer treatment, suggesting that the peptide's cytotoxic effect against cancer cells lines could be broad spectrum.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…30,31 On the other hand, this peptide also exhibited a selective cytotoxic effect against OSCC-derived cell lines CAL-27 (IC 50 ¼ 9 mM) and SCC15 (IC 50 ¼ 9 mM), while the peptide's cytotoxic effect against the non-tumorigenic cell line was moderate. 28,29 It can be seen that these IC 50 values are of the same order of magnitude as those obtained for MCF-7 cells, which conrms that the peptide exhibited signicantly selective cytotoxic effect against human cell lines derived from breast and oral cancer. The cytotoxic effect of the peptide against MCF-7, CAL-27, and SCC-15 cancer cells continues for 24 h aer treatment, suggesting that the peptide's cytotoxic effect against cancer cells lines could be broad spectrum.…”
Section: Resultssupporting
confidence: 62%
“…These results are in agreement with previous studies that suggest that the cytotoxic effect of LfcinB or peptides derived from LfcinB could be mediated by both apoptosis and/or necrosis. 28 It has also been shown that this duality in the action mechanism is dependent on the peptide concentration. The anti-tumoral activity of the tetrameric peptide LfcinB (20)(21)(22)(23)(24)(25) 4 in a hamster model was related to both apoptotic and necrotic processes; 28 the antitumoral activity of animals chronically treated with tetrameric peptide at higher concentrations was mediated mainly by apoptosis.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…26 In previous reports, it has been demonstrated that short synthetic peptides exhibited higher antibacterial, antifungal, and anticancerigenic activity than LfcinB. [26][27][28][29][30][31] The palindromic peptide LfcinB (21-25) Pal : RWQWRWQWR is a promising peptide for developing new therapeutic agents. [26][27][28][29][30] This peptide exhibits antibacterial activity against Grampositive and Gram-negative bacteria and fungi and a cytotoxic effect against oral carcinoma and breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%